Effect of Intercropping Finger Millet [Eleusine Coracana (L.) Gaertn.] With Desmodium Intortum on Striga Hermonthica Emergence across Planting Seasons - Makete , Noel N.; Gohole , Linnet S.; Opile , Wilson R.; Oduori , Chrispus A. O. (African Journal of Education,Science and Technology (AJEST), 2017)
Striga hermonthica is a major constraint affecting finger millet production in western Kenya. Yield potentials of improved finger millet varieties remain unexploited due to susceptibility to Striga. Previous studies have shown the value of intercropping maize with Desmodium spp. in efforts to control Striga. Recent studies have shown related responses when a local finger millet variety was intercropped with Desmodium spp. This study investigated the effect of intercropping Green leaf Desmodium (Desmodium intortum) with finger millet on Striga emergence and finger millet yield across two planting seasons. Trials were set up on-station at Kenya Agricultural and Livestock Research Organization’s Alupe centre (KALRO-Alupe) and on-farm at Okiludu in Teso South during the 2013 short rains and 2014 long rains seasons. Results in this study indicated no consistent evidence to show that intercropping finger millet varieties with Desmodium intortum suppressed Striga at the two sites during the two seasons tested. However,lower Striga counts were observed during the long rains season (35.9 Striga plants/plot) while higher Striga counts (151.4 Striga plants/plot) were observed during the short rains season. Finger millet yield differed significantly across planting seasons where higher yield (1.1t/ha) was observed during the long rains season and lower yield (0.6t/ha) during the short rains season. This gave a clear indication that strigolactones production may have differed across rainfall seasons. Farmers in Striga infested Alupe and Teso sub-counties are advised to consider planting finger millet during the long rains season when Striga emergence is low for better yields.